2007
DOI: 10.1021/ie0608152
|View full text |Cite
|
Sign up to set email alerts
|

Control of Crystal Density of ε-Hexanitrohexaazaisowurzitane in Evaporation Crystallization

Abstract: In the case of evaporation crystallization, the density of -hexanitrohexaazaisowurtzitane ( -HNIW, C 6 H 6 N 12 O 12 ) crystals was controlled using the evaporation rate, initial HNIW concentration, and temperature as the operating parameters. When crystal growth was promoted, the crystal density was found to deviate from the theoretical density, probably due to the inclusion of voids in the crystals that amplified the decrease in the crystal density. Thus, the crystal density was significantly reduced when th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 14 publications
2
9
0
Order By: Relevance
“…This result is consistent with the statically calculated results of low transition barriers. Hence, this coexistence should be a basis for the easy polymorphic transitions of CL-20 in solvents observed experimentally. …”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…This result is consistent with the statically calculated results of low transition barriers. Hence, this coexistence should be a basis for the easy polymorphic transitions of CL-20 in solvents observed experimentally. …”
Section: Resultsmentioning
confidence: 92%
“…The ε-form presents the highest packing density of approximately 2.04 g/cm 3 and the best stability against thermal and impact stimuli. Thus, the crystal engineering of CL-20s mainly aims to achieve an ε-formed polymorph, avoiding transformation to other less stable ones. Crystallization conditions, such as solvents, addition method, temperature, and agitation rate, can distinctively affect the polymorphs of CL-20 and their transformations. For example, polymorphs of CL-20 transform more easily in solutions than in solids.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, ultrasound effect can also diminish the size to nanoscale. [21] reports. The nano-CL-20 samples exhibit different XRD patterns, and it was found that the patterns exhibit a strong diffraction peak at 13.6 ∘ , 28.2 ∘ , and 24.1 ∘ , which corresponded to the (111), (212), and (132) crystal faces 2 of phase form (JCPDS 52-2432), demonstrating that the obtained crystal structure of nano-CL-20 was phase [22].…”
Section: Resultsmentioning
confidence: 99%
“…Four of the polymorphs (α, β, γ, and ε) exist at ambient pressure and temperature. Only ε-HNIW is applied in practice because of its good thermal stability and the highest energy density [15][16][17][18] (theoretical density of 2.044 g·cm −3 [19]). However, the ε-phase can be converted to other phases under extreme conditions [20].…”
Section: Introductionmentioning
confidence: 99%